Social Welfare: A Synthetic Analysis from the Perspective of the Main Schools of Economic Thought - Percic, Stanislav (Technium Social Sciences Journal, 2020)
The analysis of the meaning of the social welfare is a topic of great interest for researchers, as well as for policy makers. While some researchers or economists believe that social welfare is limited to the standard of living of the society, others describe it as a material and spiritual welfare of the society and make a distinction between the social welfare of those in need of a special attention from society and general welfare of the whole society. In order to understand the true meaning of the concept of social welfare, this research focuses on an incursion into the historical past of the economic thought. The aim of the present study is to analyse the social welfare or other terms related to welfare from the perspective of the main schools of economic thought. The research reveals that the representatives of the largest schools of economic thought have not overlooked terms such as prosperity, happiness, satisfaction, usefulness, wealth, building a solid foundation to what we know today as social welfare.